Challenges and Opportunities in Revitalizing Colonial Building: Barriers to Adaptive Reuse in Malaysia - Athika Norlaili Abdul Halim; Nor Syahila Ab Rashid; Noor Hayati Ismail; Mohd Aliff Izuan Md. Yasin; Nor Fatimah Abd Hamid (Semarak Ilmu Sdn Bhd, 2026)
Non-Indexed Publication